Subject of waste management fee in Poland - Huchla, Andrzej (Public Governance, Administration and Finances Law Review, 2016)
The study is dealing with selected matters of waste management regulation, especially with the applicational issues and praxis of municipalities in Poland and makes an effort to present the most neuralgic points of the normative regulation and practical experiences as well.